Diagnostic Efficacy of Radiology in the Diagnosis of Giant Cell Tumour of Bone (Delta Medical College Journal, 2014)
Background: Giant cell tumour (GCT) is an aggressive and potentially malignant lesion. Microscopic feature reveals osteoclast like giant cells in a mononuclear stromal cells background. The mononuclear stromal cell is interpreted as neoplastic. Objective: As radiological diagnosis is non invasive and cost effective in comparison to histopathological diagnosis, considering the patients compliance, the aim of the study was to observe the diagnostic efficacy of radiology in diagnosis of GCT. Materials and method: This cross sectional study was carried out in the department of Pathology, Delta Hopital Ltd., Dhaka, Bangladesh from July 2011 to December 2012. A total of 30 study subjects were enrolled in the study irrespective of age and sex. Biopsy material and relevant data of clinically suspected cases of GCT along with radiology report were sent from National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh. Histopathological diagnosis was made by expert pathologists. Results: Mean (±SD) age of the study subjects was 29.20 (±7.34) years with highest number of patients were observed in 3rd decade and female was predominant (60%) with a male female ratio of 1:1.5. Common site of GCT was around knee (50%). Among 30 clinically diagnosed GCT, 25 (83.3%) cases were radiologically diagnosed as GCT, 2 (6.7%) diagnosed as fibrous dysplasia, 1 (3.3%) as chondroblastoma, 1 (3.3%) as simple bone cyst and 1 (3.3%) as aneurysmal bone cyst. However among 30 clinically diagnosed GCT, 28 (93.3%) patients were histopathologically diagnosed as Giant cell lesion and rest 2 (6.7%) patients diagnosed as fibrous dysplasia. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of radiological diagnosis of GCT were found to be 92.6%, 100.0%, 100.0%, 40.0% and 90.0%, respectively. Conclusion: Radiology can be effectively used as a screening tool in diagnosing GCT. DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17791 Delta Med Col J. Jan 2014; 2(1): 13-16